CHARACTERIZATION OF SCHWARZ NORMS IN BANACH SPACES - OKWANY, I.O.; OKELO, N. B. (IJRDO -JOURNAL OF MATHEMATICS, 2015)
In this paper, we characterize Schwarz norms in Banach spaces. We give new results on the s-norms in B(H).